Terminal bridging of siRNA duplex at the ribose 2′ position controls strand bias and target sequence preference - Atsushi Shibata; Hisao Shirohzu; Yusuke Iwakami; Tomoaki Abe; Chisato Emura; Eriko Aoki; Tadaaki Ohgi (Molecular Therapy: Nucleic Acids, 2023)
Small interfering RNA (siRNA) and short hairpin RNA (shRNA) are widely used as RNA interference (RNAi) reagents. Recently, truncated shRNAs that trigger RNAi in a Dicer-independent manner have been developed. We generated a novel class of RNAi reagent, designated enforced strand bias (ESB) RNA, in which an siRNA duplex was chemically bridged between the 3′ terminal overhang region of the guide strand and the 5′ terminal nucleotide of the passenger strand. ESB RNA, which is chemically bridged at the 2′ positions of ribose (2′-2′ ESB RNA), functions in a Dicer-independent manner and was highly effective at triggering RNAi without the passenger strand-derived off-target effect. In addition, the 2′-2′ ESB RNA exhibited a unique target sequence preference that differs from siRNA and silenced target sequences that could not be effectively suppressed by siRNA. Our results indicate that ESB RNA has the potential to be an effective RNAi reagent even when the target sequence is not suitable for siRNA.